Construction of Fall Prevention Exercise Training Scheme for Elderly Discharged Patients Using Self-Efficacy Theory Framework - Cheng, Haiying; Shi, Ming; Pu, Fengyan (Alternative therapies in health and medicine, 2024)
We conducted this study to help older discharged patients recover better, reduce the risk of falls, and improve quality of life through self-efficacy intervention and the Otago exercise program. The purpose of this study was to address specific challenges in rehabilitation and quality of life in older patients. 60 elderly patients discharged from January 1 to June 10, 2022, were selected as the study subjects and randomly divided into the experimental group (n = 30) and the controls (n = 30). We studied the impact of a self-efficacy intervention combined with the Otago Exercise Program (OEP) in older discharged patients. We included patients aged 65 and above who understood the study protocol and randomly divided them into two groups: one group received a combined self-efficacy intervention and OEP, and the other group received only OEP treatment. The intervention period is 12 weeks, 3 times a week, 30-45 minutes each time. We focused on the exercise capacity, fall risk, quality of life, and well-being of patients in both groups after the intervention. The aim of the study was to determine whether this combined intervention could improve recovery and quality of life in older discharged patients. Comparison of clinical data between the two groups: there were no differences in gender, age, ethnicity, education, residence, family income, complications, and chronic diseases (P > .05). Self-efficacy increased significantly between the two groups after the intervention, but there was no difference before the intervention (P > .05). The self-efficacy of the experimental group was higher than that of the control group on days 15, 30, 45, and 60 (P < .05). Berg balance scale, TUG, PSMS, IADL, ADL, and total fall risk scores were significantly improved, but there was no difference before intervention (P > .05). All indicators of the experimental group were better than those of the control group on days 15, 30, 45, and 60 (P < .05). EAQ scores were significantly improved, but there was no difference between the two groups before intervention (P > .05). The EAQ of the experimental group was higher than that of the control group on days 15, 30, 45, and 60 (P < .05). This study found that a self-efficacy-based intervention combined with the Otago Exercise Program (OEP) was of value to older discharged patients. This comprehensive intervention approach can improve patients' self-efficacy, balance, walking speed, daily functioning, reduce fall risk, and improve quality of life. For healthcare providers and institutions, this means that this approach could be considered to improve the care of older discharged patients. By enhancing patients' self-efficacy and physical function, it can promote better recovery and independent living, reduce the risk of readmissions, and thus reduce the burden on the healthcare system. This study provides important practical guidance for improving the recovery and quality of life of older discharged patients.